Bijectivity of a class of Lotka-Volterra operators defined on 2D-simplex - Pah, Chin Hee; Rosli, Azizi (Springer, 2022)
It is known that if Lotka-Volterra operators, defined on the simplex Sm−1, satisfy f-monotonicity condition, then they are bijection of Sm−1. In the present paper, we consider a class of Lotka-Volterra operators defined on two dimensional simplex which are bijective, however, they are not f-monotone.